Justly balanced (Wasatiyyah): a cure for laxity or extremism in appreciation of legal rules in Islam - Mohd. Zain, Nor Razinah (LEGAS, 2014)
Justly balanced or wasatiyyah is not a new concept in Islam, but already exists alongside Islam itself. this is proven from the jurisprudential aspect of Islamic legal system itself where Islamic jurisprudence or Usul al-Fiqh is the backbone. Justly balanced is an important consideration in formulating the legal rules and laws. Such formulation of legal rules and laws can be done through the application of methods as developed under Islamic jurisprudence. In relation to such aspect, the notion of justice should be monitored where without fail; concept of justly balanced has to be present. the presence of co-related concepts of justly balanced and justice are essential in the correct application and appreciation of the legal rules or laws. Simultaneously, without fail, the sanctity of Shariah can be preserved and it is also important as to avoid legal rules or laws from leading towards injustices.